Pembuatan Video Dokumentasi Kegiatan Tim PKM-PI Universitas Dharma Andalas Melalui Media Sosial Instagram - Fathimah Zahroh; Indria Flowerina (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This final project report aims to document the activities of the Dharma Andalas University PKM-PI Team in developing an Internet of Things (IoT)-based Used Aluminium Melting Electric Furnace for UMKM's. This documentation is made as a reporting and promotional media through Instagram @pkmpi_alatpeleburaluminium by referring to Media Production Theory which includes three main stages: pre-production, production, and post-production. Instagram was chosen as the main platform because of its interactive features like Instagram Insights that enable content performance analysis. The results of this project show that the right visual communication strategy in social media can increase audience engagement and the effectiveness of information dissemination, especially in supporting technological innovation for UMKM's.